Decals prevent bird-window collisions at residences: a successful case study from Colombia: Calcomanías evitan colisiones de aves contra ventanas de residencias: estudio de un caso exitoso de Colombia (Ornitología Colombiana, 2021)
Collisions with windows are responsible for one billion annual bird deaths in the United States alone and are the second greatest cause of human-caused bird mortality. Although windows can be a significant threat to Neotropical birds, few studies have quantified collisions and none have targeted residences in this tropical region. Research in the United States and Canada has shown that residences are responsible for 44% and 90% of the window collisions, respectively. We studied bird-window collisions at a rural residence in a 4-hectare nature reserve located on the Eastern Andes piedmont in Colombia. Large and abundant windows provided attractive views but also resulted in frequent collision events, many of which were fatal. Between 2009 and 2012, we tested the effect of bird deterrent decals on collision reduction. After bird decal application on five windows (0.41 decals/m2) collisions were reduced by 84% in 36.32m2 total glass area. We show a successful case of residence-scale collision prevention to inspire other homes to stop bird mortality.